The Cost of Gender Identity Norms: Evidence from a Spouse Tax Credit - Tommaso Giommoni; Enrico Rubolino (CESifo GmbH, 2024)
This paper studies the impact of tax incentives on economic behavior within the household. We focus on an Italian tax policy that grants a large tax credit to main earners if their spouses, designated as “dependent spouses” by the tax law, report income below a certain threshold. Combining a novel administrative dataset with a bunching approach, we find that second-earner women adjust their income to benefit from the tax credit, while second-earner men do not. Second-earner women holding more conservative gender norms are the ones who mostly reduce their income. This suggests that tax policies can exacerbate economic inequalities among families and depress female labor market outcomes when they interact with entrenched gender norms.
Keywords: H24; H31; J16; J12; 330; spouse tax credit; income taxation; gender norms; bunching; household behavior; female labor supply